Design of corrugated horn antennas by evolutionary optimization techniques - Jamnejad, V; Hoorfar, A (IEEE antennas and wireless propagation letters, 2004)
Corrugated horn antennas are frequently used as the feed elements in reflector antennas for satellite and deep space communications. A particular application is the multifrequency feed horns for the reflector antennas of the JPL/NASA Deep Space Network (DSN). In this application, it is desirable to design a horn that has a nearly perfect circularly symmetric pattern (i.e., identical E- and H-plane patterns), with zero or low cross-polarization, a specified beam width, and a low return loss at the design frequency range. A parametric study of the corrugated horns, however, shows that the objective function relating the pattern shape, beam width and return loss is a nonlinear function of the corrugation dimensions with many local optima. As a result one has to resort to global optimization techniques, such as evolutionary algorithms, for successful design of such antennas. Here, an evolutionary programming (EP) algorithm is used to optimize the pattern of a corrugated circular horn subject to various constraints on return loss, antenna beam width, pattern circularity, and low cross-polarization. Examples of design synthesis for a few corrugated horns are presented. The results show excellent and efficient optimization of the desired horn parameters.